Addictions From Pathophysiology to Treatment - Belin, David (IntechOpen, 2012)
Addiction, increasingly perceived as a heterogeneous brain disorder, is one of the most peculiar psychiatric pathologies in that its management involves various, often non-overlapping, resources from the biological, psychological, medical, economical, social, and legal realms. Despite extensive efforts from the players of these various fields, to date there are no reliably effective treatments of addiction. This may stem from a lack of understanding of the etiology and pathophysiology of this disorder as well as from the lack of interest into the potential differences among patients in the way they interact compulsively with their drug. This book offers an overview of the psychobiology of addiction and its current management strategies from pharmacological, social, behavioural, and psychiatric points of view.